TiO2 and ZnO Nanoparticles in Photocatalytic and Hygienic Coatings - Veronika Jašková; Libuše Hochmannová; Jarmila Vytřasová (International Journal of Photoenergy)
Antimicrobial paints were based on the aqueous acrylic dispersion and various nanoparticles of zinc oxide and titanium dioxide. Antimicrobial ability and photoactivity were assumed in these paints. It was possible to observe the photoactivity thanks to change of organic dyes due to oxidative-reductive reaction. The best photocatalytic effect showed the coating containing the mixture of the first type of TiO2 and nano-ZnO despite the fact that the first type of TiO2 was not better in the photocatalytic test than the other types of TiO2. The agar dilution method was used to test antimicrobial ability. The Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus were chosen as test bacteria and Penicillium chrysogenum and Aspergillus niger as test molds. The antimicrobial effect of coatings with the mixture of the first type of TiO2 and nano-ZnO was the best of all the tested samples.